Development of the Canadian Women-Centred HIV Care Model Using the Knowledge-to-Action Framework. (12th April 2021) - Loutfy, Mona; Tharao, Wangari; Kazemi, Mina; Logie, Carmen H.; Underhill, Angela; O'Brien, Nadia; Pick, Neora; Kestler, Mary; H.Yudin, Mark; Rana, Jesleen; MacGillivray, Jay; Kennedy, V. Logan; et al.
In Canada, women make up 25% of the prevalent HIV cases and represent an important population of those living with HIV, as a high proportion are racialized and systemically marginalized; furthermore, many have unmet healthcare needs. Using the knowledge-to-action framework as an implementation science methodology, we developed the "Women-Centred HIV Care" (WCHC) Model to address the needs of women living with HIV. The WCHC Model is depicted in the shape of a house with trauma- and violence-aware care as the "foundation". Person-centred care with attention with attention to social determinants of health and family make up the "first" floor. Women's health (including sexual and reproductive health and rights) and mental and addiction health care are integrated with HIV care, forming the "second" floor. Peer support, leadership, and capacity building make up the "roof". To address the priorities of women living with HIV in all their diversity and across their life course, the WCHC Model should be flexible in its delivery (e.g., single provider, interdisciplinary clinic or multiple providers) and implementation settings (e.g., urban, rural).